L’école, de la transmission de la mémoire nationale au lieu de mémoire : le cas espagnol en perspective comparée - Maitane Ostolaza (Amnis)
This article studies the relations between school and nation from a historical perspective. It proposes to analyze the role played by the school institution in the nationalization process. In order to do so the school is approached from a double dimension. Firstly, it is taken as a mean of transmission of the language and the cultural contents associated with a given national community. Secondly, the school is considered, in itself, as one of the major symbols of the nation. To better understand these relationships, the Spanish case is analyzed in a comparative frame, putting it especially in relation with the republican French model, but taking also into account other South European contexts, such as the Italian, without forgetting the regional identities, like those developed in Catalonia or the Basque Country. The article makes an incursion to the study of the identity process in symbolic terms, focusing on several historical and cultural meanings attributed to the school institution.